Transformational leadership impact on innovative behaviour as perceived by healthcare workers in private hospitals in Jordan - Atef Raoush (Cogent Business & Management, 2023)
AbstractBecause of globalization and the ever-changing nature of businesses, particularly healthcare organizations, leaders need to determine the most effective method for bringing change that will help the organization achieve its objectives. Understanding how to encourage followers to reach organizational goals through leadership techniques adequately has become a concern for the healthcare business. Consequently, the significance of transformational leadership can be observed in bringing about that type of change in any business and understanding how to motivate followers to reach corporate goals effectively. As a result, the main objective of this study is to determine the influence of transformational leadership on healthcare workers’ innovative behavior in Jordan’s private hospitals as perceived by healthcare workers. This research employs a cross-sectional study design involving a quantitative method of data collection. In total, 412 healthcare workers from Jordanian private hospitals were included in the sample. Using simple linear regression analysis, the research findings revealed a significant transformational leadership impact on healthcare workers’ innovative behavior; the findings highlight the importance of hospital leaders adopting a transformational leadership style, which is crucial for motivating healthcare employees to engage in innovative behavior, In addition, Hospital leaders should focus on fostering a workplace that encourages innovation, motivates staff to gain new knowledge and skills and gives them chances to transfer their knowledge and skills into practice.